Monitoring of blood parameters under course-modified MS therapy : Substance-specific relevance and current recommendations for action - Klotz, L.; Berthele, A.; Brueck, W.; Chan, A.; Flachenecker, P.; Gold, R.; Haghikia, A.; Hellwig, K.; Hemmer, B.; Hohlfeld, R.; Korn, T.; Kuempfel, T.; et al. (Der Nervenarzt, 2016)
With the approval of various substances for the immunotherapy of multiple sclerosis (MS), treatment possibilities have improved significantly over the last few years. Indeed, the choice of individually tailored preparations and treatment monitoring for the treating doctor is becoming increasingly more complex. This is particularly applicable for monitoring for a treatment-induced compromise of the immune system. The following article by members of the German Multiple Sclerosis Skills Network (KKNMS) and the task force "Provision Structures and Therapeutics" summarizes the practical recommendations for approved immunotherapy for mild to moderate and for (highly) active courses of MS. The focus is on elucidating the substance-specific relevance of particular laboratory parameters with regard to the mechanism of action and the side effects profile. To enable appropriate action to be taken in clinical practice, any blood work changes that can be expected, in addition to any undesirable laboratory findings and their causes and relevance, should be elucidated.
EVALuna2:22467